Frontiers of policy and governance research in a smart city and artificial intelligence: an advanced review based on natural language processing - Dong, Liang; Liu, Yunhong (Frontiers in Sustainable Cities, 2023)
This study presents an advanced review of policy and governance research in the context of smart cities and artificial intelligence (AI). With cities playing a crucial role in achieving the United Nations Sustainable Development Goals, it is vital to understand the opportunities and challenges that arise from the applications of smart technologies and AI in promoting urban sustainability. Using the Latent Dirichlet Allocation (LDA) method based on a three-layer Bayesian algorithm model, we conducted a systematic review of approximately 3700 papers from Scopus. Our analysis revealed prominent topics such as “service transformation,” “community participation,” and “sustainable development goals.” We also identified emerging concerns, including “open user data,” “ethics and risk management,” and “data privacy management.” These findings provide valuable insights into the current progress and frontiers of policy and governance research in the field, informing future research directions and decision-making processes.